A simple probe with visible color change for selective detection of cysteine. Issue 9 (20th October 2020) - Yin, Hai-Feng; Gao, Meng-Jiao; Jiang, Wen-Jing; Gan, Yu-Han; Li, Chen; Kang, Yan-Fei; Meng, Ya-Li; Xin, Zhen-Hui
Abstract: In this work, we synthesized a simple fluorescent probe, which can selectively detect cysteine. With addition of cysteine, the probe solution showed marked color change from pale yellow to orange color by naked eye. There was an excellent linear relationship between fluorescence intensity of probe and cysteine concentration. Moreover, the probe displayed satisfactory detection limit. Low toxicity and cellular imaging offered the important conditions for detecting cysteine in biological system.